Analisis Adekuat Antara Asupan Vitamin D Dengan Demensia Pada Lansia Di Wilayah Kerja Puskesmas - Aqilla Squeare Fauzi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2023)
Based on population projection data, it is estimated that in 2017 there will be 23.66 million elderly people in Indonesia (9.03%). The number of elderly people is predicted in 2020 (27.08 million), 2025 (33.69 million), 2030 (40.95 million) and 2035 (48.19 million) (Ministry of Health RI, 2017). The prevalence of dementia (per 1000 people) in Indonesia in 2005 was 191.4 incidents, in 2020 it is estimated to be 314.1 incidents, and will increase in 2050 to around 932 incidents. The data obtained in the work area of ​​the Telaga District Public Health Center were 134 elderly, of which 38 had dementia. From the results of interviews obtained from health workers at the puskesmas and families, they said that often the elderly forgot many activities such as bathing, taking medicine and others, so the family had to remind them to take a bath, take medicine and so on. Further interviews conducted by researchers on the elderly, some said that they rarely consume vitamins, especially vitamin D, are lazy to exercise, do light activities or sunbathe every morning which can increase the risk of developing dementia.